The Rondonian-San Ignacio Province in the SW Amazonian Craton: An overview - Bettencourt, Jorge Silva; Leite, Washington Barbosa [UNESP]; Ruiz, Amarildo Salina; Matos, Ramiro; Payolla, Bruno Leonelo; Tosdal, Richard M. (Pergamon-Elsevier B.V. Ltd, 2010)
The Rondonian-San Ignacio Province (1.56-1.30 Ga) is a composite orogen created through successive accretion of arcs, ocean basin closure and final oblique microcontinent-continent collision. The effects of the collision are well preserved mostly in the Paragua Terrane (Bolivia and Mato Grosso regions) and in the Alto Guapore Belt and the Rio Negro-Juruena Province (Rondonia region), considering that the province was affected by later collision-related deformation and metamorphism during the Sunsas Orogeny (1.25-1.00 Ga). The Rondonian-San Ignacio Province comprises: (1) the Jauru Terrane (1.78-1.42 Ga) that hosts Paleoproterozoic basement (1.78-1.72 Ga), and the Cachoeirinha (1.56-1.52 Ga) and the Santa Helena (1.48-1.42 Ga) accretionary orogens, both developed in an Andean-type magmatic arc; (2) the Paragua Terrane (1.74-1.32 Ga) that hosts pre-San Ignacio units (>1640 Ma: Chiquitania Gneiss Complex, San Ignacio Schist Group and Lomas Manechis Granulitic Complex) and the Pensamiento Granitoid Complex (1.37-1.34 Ga) developed in an Andean-type magmatic arc; (3) the Rio Alegre Terrane (1.51-1.38 Ga) that includes units generated in a mid-ocean ridge and an intra-oceanic magmatic arc environments; and (4) the Alto Guapore Belt (<1.42-1.34 Ga) that hosts units developed in passive marginal basin and intra-oceanic arc settings. The collisional stage (1.34-1.32 Ga) is characterized by deformation, high-grade metamorphism, and partial melting during the metamorphic peak, which affected primarily the Chiquitania Gneiss Complex and Lomas Manechis Granulitic Complex in the Paragua Terrane, and the Colorado Complex and the Nova Mamore Metamorphic Suite in the Alto Guapore Belt. The Paragua Block is here considered as a crustal fragment probably displaced from its Rio Negro-Juruena crustal counterpart between 1.50 and 1.40 Ga. This period is characterized by extensive A-type and intra-plate granite magmatism represented by the Rio Crespo Intrusive Suite (ca. 1.50 Ga), Santo Antonio Intrusive Suite (1.40-1.36 Ga), and the Teotonio Intrusive Suite (1.38 Ga). Magmatism of these types also occur at the end of the Rondonian-San Ignacio Orogeny, and are represented by the Alto Candeias Intrusive Suite (1.34-1.36 Ga), and the Sao Lourenco-Caripunas Intrusive Suite (1.31-1.30 Ga). The cratonization of the province occurred between 1.30 and 1.25 Ga. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: SW Amazonian Craton; Rondonian-San Ignacio Province; Mesoproterozoic evolution; Accretionary belts; Collisional orogeny